2021
DOI: 10.3390/diagnostics11040603
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Innovative and Traditional Cardiometabolic Indices in Estimating Atherosclerotic Cardiovascular Disease Risk in Adults

Abstract: This study aimed to investigate the performance of innovative and traditional cardiometabolic indices, including body mass index (BMI), waist circumference (WC), Chinese visceral adiposity index (CVAI), visceral adiposity index, lipid accumulation product, a body shape index (ABSI), body roundness index, conicity index (CI), triglyceride-glucose (TyG) index, TyG-BMI, and TyG-WC, in estimating atherosclerotic cardiovascular disease (ASCVD) risk in 3143 Taiwanese adults aged 20–79 years. Elevated 10-year ASCVD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 50 publications
3
21
2
Order By: Relevance
“…In a recent cross-sectional study, CVAI showed the strongest association with cardiovascular disease among the commonly used abdominal obesity indices (30). Similarly, several other studies have demonstrated that CVAI is related to cardiovascular risk or its risk factors, such as carotid atherosclerosis (31)(32)(33). Our study extends this field by demonstrating an association between CVAI and incident renal damage.…”
Section: Discussionsupporting
confidence: 82%
“…In a recent cross-sectional study, CVAI showed the strongest association with cardiovascular disease among the commonly used abdominal obesity indices (30). Similarly, several other studies have demonstrated that CVAI is related to cardiovascular risk or its risk factors, such as carotid atherosclerosis (31)(32)(33). Our study extends this field by demonstrating an association between CVAI and incident renal damage.…”
Section: Discussionsupporting
confidence: 82%
“…The study found that CVAI was more effective than various cardiometabolic indices, including BMI, WC, VAI, LAP, ABSI, triglyceride-glucose (TyG) index, TyG-BMI, and TyG-WC. 33 Thus, CVAI is a better predictor of the state of visceral fat than conventional obesity indicators. Therefore, this study suggests that CVAI is a valuable predictive biomarker for new-onset T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…BAI is a marker of adipose function and distribution, and LAP is associated with insulin resistance, reflecting central fat accumulation ( 29 , 30 ). Additionally, mounting evidence supports that these visceral obesity-related indices better identify individuals at elevated risk for metabolic diseases such as T2DM and CVD ( 31 ). For instance, LAP is a better predictor of 10-year cardiovascular events than BMI, and WC and LAP are simple and accurate predictors for metabolic syndrome in undiagnosed adults ( 29 , 32 ).…”
Section: Discussionmentioning
confidence: 99%